Estimation of exercise tolerance in bike track racing based on analysis of heart rate variability in athletes of various level of training - Bakayev, V.; Bolotin, A. (Scientific Journal of Sport and Performance, 2022)
Assessment of the tolerance of the training load by cyclists who participate in track races is a significant indicator of the adaptive reactivity of the athletes' bodies. The circulatory system of athletes, during cycling races on the track, is subject to colossal functional loads, both during training work and during competitions. The basis of the training process of female cyclists is adaptation to the effects of physical activity, which has a stimulating effect on the course of adaptive reactions of the organism of female athletes in preparation for the competition. A necessary list of heart rate variability indices has been formed, characterizing the degree of tolerance of the training load by cyclists during preparation for competitions on the track. A procedure has been developed for testing the characteristics of the heart rate variability at rest and during the aftereffect of physical activity on the body of cyclists. The results of the influence of the nervous and hormonal regulation of the heart rate on the fitness state of female cyclists are presented. It has been proven that the main indicator of the fitness level of female cyclists is the synchronization of the influence of the nervous and hormonal components of the regulation of the heart rate. The results obtained allow us to recommend the assessment of the degree of synchronization of the nervous and hormonal components of the regulation of the heart rate as the main indicator of the exercise tolerance of cyclists.